Horizontal implementation of expectation-maximization algorithm in SQL for performing clustering in very large databases - ORDONEZ CARLOS; CEREGHINI PAUL M (2003)
A method for performing cluster analysis inside a relational database management system. The method defines a plurality of tables for the storage of data points and Gaussian mixture parameters and executes a series of SQL statements implementing an Expectation-Maximization clustering algorithm to iteratively update the Gaussian mixture parameters stored within the tables.